2001
DOI: 10.1103/physrevlett.86.71
|View full text |Cite
|
Sign up to set email alerts
|

Jamming of Granular Flow in a Two-Dimensional Hopper

Abstract: We study experimentally the jamming phenomenon of granular flow of monodisperse disks of D = 5 mm diameter in a two-dimensional hopper with opening R. The jamming probability J(d) is measured where d identical withR/D. We found that J(d) decreases from 1 to zero when d increases from 2 to 5. From observing the disk configurations of the arch in the jamming events, the jamming probability can be explained quantitatively by treating the arch as the trajectory of a restricted random walker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
357
5
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(381 citation statements)
references
References 4 publications
18
357
5
1
Order By: Relevance
“…To et al [13], To and Lai [14] reported that clogging arches have a semi-circular convex shape, which can be reproduced by a restricted random walk model. Note that a convex shape is, indeed, a necessary condition for the static equilibrium of The big white square marks the zone that has been considered as the bulk region, as justified in the text.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To et al [13], To and Lai [14] reported that clogging arches have a semi-circular convex shape, which can be reproduced by a restricted random walk model. Note that a convex shape is, indeed, a necessary condition for the static equilibrium of The big white square marks the zone that has been considered as the bulk region, as justified in the text.…”
mentioning
confidence: 99%
“…In all these systems clogging arches withstand the weight of the particles above them just as architectural arches do. For the case of silos, a link has been sought between the properties of the arches and the clogging probability [13,14,22,23]. Although the relationship is not fully understood, the knowledge about the properties of these assemblies has been notably improved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The surface of grains is usually rough, thus leading to speciÿc angles of repose [11]. Also, the grain anisotropy leads to phenomena like jams [12], in ow, and arches [13], in static structures. It seems therefore necessary to have at least one degree of freedom in order to describe grains; we are even aware that only one degree is a very strong approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative predictions for flow rates were proposed (e. g. [5][6][7][8] and references therein). When the outlet diameter is smaller than about 5 particle diameters [9][10][11][12][13], clogs form after some time at the orifice and block further outflow, mostly unwanted. Spontaneous arch formation [14,15], the preceding kinetics [16], as well as the inherent force distributions [17,18] have been analyzed in the literature.…”
mentioning
confidence: 99%